Transfer of tactile input from an artificial hand to the forearm: experiments in amputees and able-bodied volunteers. (May 2013) - Antfolk, Christian; Cipriani, Christian; Carrozza, Maria Chiara; Balkenius, Christian; Björkman, Anders; Lundborg, Göran; Rosén, Birgitta; Sebelius, Fredrik
<x xml:space="preserve">Abstract</x> Purpose: This study explores the possibilities of transferring peripheral tactile stimulations from an artificial hand to the forearm skin. Method: A tactile display applied to the forearm skin was used to transfer tactile input to the forearm from various locations on a hand displayed on a computer screen. Discernment of location, levels of pressure and a combination of the two in simulated functional grips was tested to quantify the participants' ability to accurately perceive the tactile stimulations presented. Ten participants (5 forearm amputees and 5 able-bodied volunteers) unfamiliar with the equipment participated in the three-stage experiments comprising a learning session with vision, a reinforced learning session without vision and a validation session without vision. Results: The location discernment accuracy was high in both groups (75.2% and 89.6% respectively). The capacity to differentiate between three different levels of pressure was also high (91.7% and 98.1% respectively in the two groups). Recognition of simulated grip was slightly more difficult with the groups scoring 58.7% and 68.0% respectively for accuracy in the validation session. Conclusions: This study demonstrates that it is possible, following a brief training period, to transfer tactile input from an artificial hand to the forearm skin. The level of accuracy was lower for the more complex task, simulated grip recognition, possibly because this represents a more complex task requiring higher order brain functions. These results could form the basis for developing sensory feedback in hand prostheses.